2003
DOI: 10.1111/j.1348-0421.2003.tb02796.x
|View full text |Cite
|
Sign up to set email alerts
|

Terminal Restriction Fragment Length Polymorphism Analysis for Human Fecal Microbiota and Its Application for Analysis of Complex Bifidobacterial Communities

Abstract: A large number and variety of bacteria exist in the human intestinal tract. The balance of the intestinal microbiota closely relates to the health of the individual. Hence, understanding the human intestinal microbiota is very important. Traditional methods to determine the composition of the intestinal microbiota require various culture techniques, which are time-consuming and laborious. Therefore, many researchers used various culture-independent methods; including 16S rRNA probe hybridization (3, 23), PCR-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
83
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 91 publications
(85 citation statements)
references
References 35 publications
2
83
0
Order By: Relevance
“…The procedure is outlined in Figure 1 and used primers are shown in Table 1. The bacterial 16S rDNA was amplified by PCR using 5'-6 -carboxyfluorescein (6 -FAM) -labeled 27F primer and 1492R primer except for Bifidobacterium (7). Then, PCR products were digested with restriction enzymes HhaI and MspI, and 5'-labeled restriction fragments were examined in a genetic analyzer.…”
Section: Culture-independent Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The procedure is outlined in Figure 1 and used primers are shown in Table 1. The bacterial 16S rDNA was amplified by PCR using 5'-6 -carboxyfluorescein (6 -FAM) -labeled 27F primer and 1492R primer except for Bifidobacterium (7). Then, PCR products were digested with restriction enzymes HhaI and MspI, and 5'-labeled restriction fragments were examined in a genetic analyzer.…”
Section: Culture-independent Methodsmentioning
confidence: 99%
“…In our previous studies, intestinal microbiota was analyzed according to the method of Sakamoto et al (7). The procedure is outlined in Figure 1 and used primers are shown in Table 1.…”
Section: Culture-independent Methodsmentioning
confidence: 99%
“…This method has also been successfully applied for the assessment of diversity of human oral microbiota and rapid comparison of the community structure between subjects with and without periodontitis (33). In addition, it has been demonstrated that T-RFLP analysis is useful for assessment of the diversity of the human fecal microbiota and rapid comparison of the community structure among individuals (13,32). T-RFLP analysis revealed differences among bacterial populations present in mucosa and lumen of the chicken ileum and cecum (8,9).…”
mentioning
confidence: 99%
“…The difference in size of a restriction fragment between that predicted and that observed has been shown in many species of bacteria (24,25). Realtime PCR results did not correlate with T-RFLP results (Table 1).…”
Section: Fragment Of C Scindens In T-rflp Analysis and Cell Numbers mentioning
confidence: 71%
“…When the target of PCR is 16S ribosomal DNA, the terminal restriction fragments pattern reflects the taxonomic diversity of the bacteria in the sample. T-RFLP is a rapid and efficient approach for successfully obtaining profiles of the various members of a complex microbial community, for example, human feces (10,25), chicken cecal samples (6), pig colon (19), rat feces (15), oral bacterial flora (24), soil (20,21), and marine sediments (28). The present study is the first to our knowledge to analyze 40 fecal samples using T-RFLP and to compare them using a dendrogram.…”
mentioning
confidence: 99%